Prospective Clinical Trial of Surgical Intervention for Painful Rib Fracture Nonunion. Issue 6 (June 2014) - Fabricant, Loic; Ham, Bruce; Mullins, Richard; Mayberry, John
We performed a prospective clinical trial of resection with or without plate fixation for symptomatic rib fracture nonunion three or more months postinjury with 6-month postoperative followup. The McGill Pain Questionnaire (MPQ) and RAND 36 Health Survey were administered and activity level (sedentary, ambulatory, moderately active, vigorous), functional status (disabled, nonphysical labor, physical labor), and work status (employed, unemployed, retired, student) were queried pre- and postoperatively. Twenty-four patients 4 to 197 months (median, 16 months) postinjury underwent surgical intervention for one to four rib fracture nonunions (median, two nonunions). Evidence of intercostal nerve entrapment was present in nine patients (38%). MPQ Present Pain Intensity and Pain Rating Index and RAND 36 Physical Functioning, Role Physical, Social Functioning, Role Social, Bodily Pain, Vitality, Mental Health, and General Health were significantly improved at six months compared with study entry ( P < 0.05). Activity levels significantly improved ( P < 0.0001) but functional and work status did not change. Twenty-four-hour morphine equivalent dosage of opioids at study entry was 20.3 ± 30.8 (mean ± standard deviation) and at study completion was 9.4 ± 17.5 ( P = 0.054). Complications included one wound infection, two partial screw backouts, and one chest wall hernia at one year after resection of adjacent nonunions with significant gaps repaired with absorbable plates. Surgical intervention for rib fracture nonunion may improve chronic pain and disability but without change in functional or work status. Resection of adjacent nonunions with significant gaps may lead to chest wall hernia.